A pilot randomized controlled trial of a technology-based substance use intervention for youth exiting foster care. (November 2018) - Braciszewski, Jordan M.; Tzilos Wernette, Golfo K.; Moore, Roland S.; Bock, Beth C.; Stout, Robert L.; Chamberlain, Patricia
Abstract: Youth exiting foster care represent a unique, at-risk population in that they receive supportive health services while under the umbrella of the foster care system, but access to care can drop precipitously upon release from foster custody. Traditional means of substance use treatment may not meet the needs of this vulnerable population. Mobile interventions, however, have demonstrated high acceptability and efficacy across a range of mental and physical health issues. The specific advantages to mobile interventions dovetail well with the barriers faced by youth exiting foster care. This study describes the feasibility, acceptability, and initial efficacy of iHeLP, a computer- and mobile phone-based intervention based in Motivational Interviewing for reducing substance use among youth exiting foster care ( n = 33). Participants were randomly assigned to either iHeLP or a contact control, each of which lasted six months. Feasibility was evaluated through eligibility and enrollment rates at baseline, and retention and intervention reach rates 3, 6, 9, and 12 months later. Acceptability was measured through a 5-item satisfaction measure and exit interviews. The two groups were then compared on a monthly measure of substance use. Study enrollment, retention, response rate, engagement, and satisfaction were all very good. Participants receiving iHeLP reported higher percent days abstinent than the control group, with effect sizes ranging from 0.32 to 0.62. Technology-based interventions such as iHeLP may be attractive to this population and support efforts towards reductions in substance use. Highlights: Youth who have experienced foster care report high levels of substance use. Traditional approaches to substance use service provision may not meet the unique needs of this population. We developed a computer- and mobile phone-based intervention for reducing substance use among youth exiting foster care. Feasibility, acceptability, and preliminary efficacy were strong. Technology-based interventions may be an engaging alternative to reduce substance use among youth exiting foster care.